Processing of date palm kernel(DPK)for production of Edible Jam - Mirghani, Mohamed Elwathig Saeed; Al-Mamun, Abdullah; Mustafa, Simma Mahirah (2010)
This project involved the usage of date palm (Phoenix dactylifera) kernel (DPK) to be produced as an edible jam after had been grounded into powder. DPK jams was prepared by adding date palm kernel (DPK) powder, saccharose, pectin, water, citric acid, ascorbic acid and Gum Arabic. Then the experiment design for date palm kernel (DPK) for production of jam was done using the Design Expert. The design shows that there were ten types of jams to be produce according to the content of different material where the parameters such as amount of saccharose, pectin and dietary fiber from Gum Arabic were varied to give the best acceptability of the DPK jams samples. After that the jams sample produce were evaluated in terms of the sensory evaluation which includes taste, texture, aroma, appearance and overall acceptability by the ten panelist selected from students of Biochemical-Biotechnology Engineering, International Islamic University Malaysia. The samples were evaluated based on a five point hedonic scale, where one represented ‘‘disliked extremely” and five represented ‘‘liked extremely”. All the data then were analyzed by using spreadsheet Microsoft Excel. From the result showed that some of the panelists accept the product while the others reject the DPK jam samples. Finally, this report is the outcome of the research done to find the acceptability of the production of DPK jams.